Interwoven Emotions in the Development of Creative Processes: EcoeducaSustainable, an Educational Innovation Project - Soler, Seila; Rosser, Pablo (Angstrom Centre of Education, 2024)
The research examines the role of emotions in creativity within educational environments, emphasizing the influence of sustainability education on adolescent students. Utilizing the Positive and Negative Affect Schedule (PANAS), the study explores how emotions impact students' well-being and academic achievements, advocating for early emotional assessments. Central to the research is the EcoeducaSustainable project, which integrates sustainability education to study its effect on emotional responses and creativity. The project employs Spearman's Rho to reveal complex emotional dynamics, offering insights on how to enhance educational strategies through emotional engagement. The findings highlight the importance of addressing emotions in education, particularly for fostering environments conducive to creativity and sustainable learning. This work significantly contributes to the fields of emotional intelligence, creativity, and sustainability in education.